The Patriot Press and their Paper Tiger: Community Formation and Allusions to the Patriot Hunters, 1836-1842 - Smith, Stephen (Ontario History, 2023)
While a major focus in studies of the Rebellion has been the secret society the Patriot Hunters, one understudied aspect to the Rebellion is the continued role of allied newspapers in organizing rebellion in the Canadas and subsequently sustaining it in exile. The article provides an overview of the “patriot press” and how it helped delineate the patriot movement in exile. In the press, terms and language associated with the Patriot Hunters provided a tool to unite patriots. While some patriot editors expressed aversion to secrecy, some of those same editors now used references to secret organizing as ploys to reassure readers that they were part of a larger, highly active, and highly successful organization committed to Canadian independence—even if that was not true.